When Icon Enters the Realm of Religion: Tracing the Idea of Iconoclasm in Islamic Tradition - M. Amin Nurdin; M. Tamamul Iman; Salman Al Farisi (Mimbar Agama Budaya, 2025)
This research aims to trace the ideas of iconoclasm that have grown within the Islamic tradition. It is motivated by the relationship between religion and icons, which has sparked considerable debate. On one hand, there are some religions that consider icons a legitimate element in their religious tradition, a practice known as iconodulism. On the other hand, there are religions that take the opposite stance, rejecting, prohibiting, or even condemning the use or production of icons within their religious tradition, a practice known as iconoclasm. In the context of Islam, some argue that iconoclastic movements are often directed at specific groups as a purification effort. However, upon closer examination, many dominant traditions within Islam have elements of iconoclasm: Allah is symbolized through the concept of Asma` al-Husna or depicted through calligraphic art; the visualization of Prophet Muhammad has been a controversial subject, leading to an evolution that is symbolized through light or calligraphy. There is also a stigma attached to painting and sculpture in this context. Why does Islamic tradition prefer symbols over icons?.